2010
DOI: 10.1097/ana.0b013e3181cd318b
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Pial Vascular Changes Under Propofol or Sevoflurane Anesthesia During Global Cerebral Ischemia and Reperfusion in Rabbits

Abstract: Propofol and sevoflurane acted differently on pial vessels during reperfusion after ischemic insult. Pial arterioles and venules did not dilate immediately after reperfusion, and subsequently constricted throughout the reperfusion period in propofol-anesthetized rabbits. In contrast, pial arterioles and venules dilated temporarily and returned to baseline in sevoflurane-anesthetized rabbits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 17 publications
2
23
0
Order By: Relevance
“…i levels through NMDA receptors and reduce glutamate-induced injury which contributed to neuroprotection, but ketamine and propofol-induced neuroprotection showed opposite dose-dependent relationship in this study. Ketamine, unlike propofol, predominantly inhibits excitatory neurotransmission at glutamatergic synapse, increases cerebral metabolic rate for O 2 (CMRO 2 ), cerebral blood flow (CBF) and intracranial pressure (ICP), but propofol has significant effects on c-aminobutyric acid (GABA A ) receptors and decreases CBF and CMRO 2 , and mitigates ICP [4]. Therefore, it is feasible to assume that each agent enhance its inherent effect on cerebral ischemic injury with concentrations increasing.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…i levels through NMDA receptors and reduce glutamate-induced injury which contributed to neuroprotection, but ketamine and propofol-induced neuroprotection showed opposite dose-dependent relationship in this study. Ketamine, unlike propofol, predominantly inhibits excitatory neurotransmission at glutamatergic synapse, increases cerebral metabolic rate for O 2 (CMRO 2 ), cerebral blood flow (CBF) and intracranial pressure (ICP), but propofol has significant effects on c-aminobutyric acid (GABA A ) receptors and decreases CBF and CMRO 2 , and mitigates ICP [4]. Therefore, it is feasible to assume that each agent enhance its inherent effect on cerebral ischemic injury with concentrations increasing.…”
Section: Discussionmentioning
confidence: 98%
“…Propofol (2,6-diisopropylphenol) and ketamine (phenylcyclohexyl-piperidine) are established nonbarbiturate anesthetic agents, commonly used in the clinical practices. Propofol is considered to be a neuroprotective agent against cerebral ischemia based on the assumption that it has the ability to decrease cerebral blood flow (CBF) in conjunction with a reduction of cerebral metabolic rate for O 2 (CMRO 2 ) and intracranial pressure (ICP) [1][2][3][4]. Recent studies showed that propofol improves neurological outcome and decreases infarct size in animal models of cerebral ischemia [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of various chemical substances (Cantu & Hegsted, 1970) on the brain nerve tissue damaged by ischemia as well as various pathological and pathophysiological changes induced by the total cerebral ischemia in rabbits and other laboratory animals are the subject of many studies (Ishiyama et al, 2010). The place of origin of the truncus brachiocephalicus and the a. subclavia sinistra are most commonly used to induce the total cerebral ischemia by ligation (Hossmann 1998;Iwama et al, 2000;Pluta, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…are clinical scenarios in which brain ischemia and reperfusion could occur under propofol anesthesia. Global brain ischemia-reperfusion during propofol anesthesia provokes persistent cerebral pial constriction [7]. Cerebral vasoconstriction possibly exacerbates ischemic brain injury [8].…”
Section: Introductionmentioning
confidence: 99%